Optoelectrical Method of Measuring the Aircraft Track Velocity Vector - Ricny, V.; Mikulec, J. (Radioengineering Society, 1992)
This article deals with new principal and basic algorithm of the optoelectronics measuring method of aircraft track velocity vector using digital processing of video signals of CCD line sensors.